Entering university experience and selfregulated learning among undergraduate students - Mohd. kosnin, Azlina (Serials Publications, 2016)
The present research explored the experiences of students as they reflect about their transition from pre-university to university level. Moreover, self-regulation in studies that ensued as a consequence of university life was also explored. Five successful final-year undergraduate female students took part in a focus group discussion. A modified and limited version of grounded theory method was used to analyze the generated narrative. The participants reported that entering a university was quite a novel, challenging as well as exciting experience for them. They had to adapt their study strategies as per requirements. Focus on present and future goals helped regulate themselves to be on their successful educational track. Self monitoring and self reinforcement were found to be important aspects of self-regulation. Fears also played a role in self-regulated learning of students. The goals and fears of students were individualistic and collectivistic in type. Individualistic goals and fears were related to the personal life of the students' self, whereas collectivistic goals and fears were related to their family and societal milieu. The collectivistic aspect of self-regulated learning, found in this study, can be considered a new direction in the field which can be quite relevant to collectivistic cultures.